Komunikasi Pemerintah Dan Fragmentasi Opini Publik Di Media Sosial: Kasus Program Makan Bergizi Gratis - Sarah Pamela; Mulharnetti Syas (Khazanah Multidisiplin, 2026)
The Free Nutritious Meals Program (MBG) is one of the Indonesian government's strategic policies in an effort to improve nutrition and human resources. However, the implementation and communication of this policy takes place in the context of social media, which is characterized by openness of information and fragmentation of public opinion. This study aims to analyze how the government's communication regarding the Free Nutritious Meals Program takes place on social media and how fragmentation of public opinion is formed in response to this policy. This study uses a qualitative approach with a document study design and secondary social media data analysis. Data were obtained from official government documents, the national Free Nutritious Meals Program dashboard, and public posts and comments on social media platforms. The analysis was conducted thematically using the perspective of political public relations in the social media era as proposed by Kara Alaimo. The results show that although the government has communicated the MBG through data-based narratives and statistical visualizations, social media has become an arena for reinterpreting policy messages, resulting in the fragmentation of public opinion. Public opinion is divided into various clusters influenced by local experiences, emotions, and perceptions of policy implementation. These findings confirm that government communication in the social media era faces structural challenges in the form of a loss of narrative control and a tendency toward reactive communication. This study concludes that data-based policy communication needs to be complemented by communication strategies that are adaptive to the dynamics of social media in order to manage the fragmentation of public opinion and strengthen policy legitimacy.